PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA BADAN PENGURUS DAERAH GAPENSI ACEH - Yusni Hervy Yusuf; Junaidi Junaidi (SI-MEN, 2022)
This study aims to analyze competence and work discipline on employee work productivity at the Gapensi Aceh Regional Management Board. The sample of this research is the employees of the Aceh Gapensi Regional Management Board, totaling 15 employees using the census technique. Data analysis used statistical analysis of correlation and multiple regression models with the help of SPSS 25 software. To test each item on each variable, validity and reliability tests were carried out on the instrument. The results of the analysis show that simultaneously there is an influence between competence and work discipline on employee work productivity. The results of the F test obtained Fcount > Ftable or (29.975> 3.41) and the significant test was that the p value was 0.000 < p which was set at 0.05 which means significant. Partial test results show that: 1. competence has an effect on employee work productivity with Tcount 2.144 > Ttable 1.770 and p value 0.005 < p 0.00 means significant. 2. Work discipline affects employee work productivity with Tcount 2.996> Ttable 1.770 with a p value of 0.009 of <0.05 means significant. Thus the effect of work discipline has a stronger influence on employee work productivity than competence. The results of the coefficient of determination of 83.3% indicate that the ability of the independent variables (competence and work discipline) to explain the dependent variable (employee work productivity) and the rest are other variables not explained in this study.